In Vitro Ovine Embryo Culture: Effectiveness of TCM-199 in Combination with 17?-Estradiol Hormone and Co-Culture of FTEC - Yon Soepri Ondho; Dela Ayu Lestari; Daud Samsudewa (Jurnal Veteriner, 2020)
Objective of this research was to determine the effectiveness of various culture mediums on thecleavage to morula in in vitro embryo culture of ovine. A total of 1.064 zygotes (fertilized oocytes) were grown in three kinds of different embryo culture medium, which were Tissue Culture Medium 199 (TCM-199) (T1), TCM-199 + 17â-estradiol (T2) and TCM-199 + co-culture of Fallopian Tube Epithelial Cell (FTEC) (T3). Data were analyzed using a completely randomized design with ANOVA analysis and HonestlySignificant Difference test. The variable observed were the percentage of embryo cleavage and morula. Results showed that T3 had the highest percentage (72.45%) of the cleavage occurred in zygotes cultured in the TCM-199 + FTEC co-culture medium, as well as embryo growth to the morula stage (75.75%). Incontrast, zygotes cultured in T1 and T2 had lower cleavage and lower morula development than T3, as much as 27.38%; 47.82% and 58.15%; 66.66%, respectively. In conclusion, TCM-199 + FTEC co-culture medium is the best medium for embryo culture.